2019
DOI: 10.1111/coa.13305
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of 4‐hour delayed‐enhanced 3D‐FLAIR MR images in sudden hearing loss

Abstract: Objective The aim of this study was to investigate the clinical significance of 4‐hour delayed‐enhanced 3.0 Tesla (3T) 3D‐fluid‐attenuated inversion recovery (FLAIR) MR imaging in sudden sensorineural hearing loss (SSNHL). Study design Case series with comparisons. Setting Tertiary referral centre. Participants Eighty‐seven idiopathic SSNHL patients were enrolled between January 2015 and December 2016 and received high dose steroid therapy and intratympanic steroid injections as salvage treatment. Intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Kim et al (36) also showed no significant difference in signal intensity in the affected ears. However, Byun et al (37) and Min et al (38) suggested that the higher signal intensity observed in ISSNHL patients 4 h after Gd indicated a poor prognosis. Byun et al (37) claimed that a higher signal intensity was shown in 4-h Gd-injection imaging than that in 10-min imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al (36) also showed no significant difference in signal intensity in the affected ears. However, Byun et al (37) and Min et al (38) suggested that the higher signal intensity observed in ISSNHL patients 4 h after Gd indicated a poor prognosis. Byun et al (37) claimed that a higher signal intensity was shown in 4-h Gd-injection imaging than that in 10-min imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, Byun et al (37) and Min et al (38) suggested that the higher signal intensity observed in ISSNHL patients 4 h after Gd indicated a poor prognosis. Byun et al (37) claimed that a higher signal intensity was shown in 4-h Gd-injection imaging than that in 10-min imaging. The increased signal intensity caused by increased permeability (due to BLB) suggested an increase in inner ear damage.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies of the prognostic factors for ISSNHL. [13][14][15] One study reported that hearing outcomes were poorer in subjects presenting late and in those with associated diabetes or hypertension. 9 Another study suggested that prognostic factors were age, initial hearing threshold, speech performance scores before treatment, descending-type audiogram, and coexistence of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies of the prognostic factors for ISSNHL 13–15 . One study reported that hearing outcomes were poorer in subjects presenting late and in those with associated diabetes or hypertension 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, post-contrast 3D FLAIR MRI findings showed high sensitivity and encouraging prognostic value in several studies. 20,21) An enhancement in the post-contrast 3D FLAIR MRI can demonstrate loosening of the BLB. Although both pre-contrast 3D FLAIR MRI and post-contrast 3D FLAIR MRI can reflect on the integrity of BLB, care should be taken to differentiate between them since the visualized pathology is different.…”
Section: Discussionmentioning
confidence: 99%